Immune response to autologous transfusion in healthy volunteers: WB versus packed RBCs and FFP - Frietsch, Thomas; Fessler, Heiko; Kirschfink, Michael; Nebe, Carl Thomas; Waschke, Klaus F.; Weiler-Lorentz, Arnulf (Transfusion, 2001)
BACKGROUND: Storage of blood as packed RBCs and FFP is standard practice in allogeneic transfusion. Separation into components has been proposed for autologous transfusion, as well, but beneficial effects have not yet been shown. STUDY DESIGN AND METHODS: Twenty-four healthy male volunteers were randomly assigned to receive 1 unit of either autologous RBCs and FFP (RCP group) or WB (WB group) after 49 or 35 days of storage, respectively. The immune response was analyzed by ELISA for IL-6, C3a, terminal complement complex SC5b-9, TNF-alpha, and neopterin. Differential WBC counts and the phagocytosis of neutrophils and monocytes were measured by flow cytometry. RESULTS: Cell counts of monocytes (0.85 x 10(3) ng/microL) [corrected] and neutrophils (6.9 x 10(3) ng/microL) [corrected] increased 30 minutes after WB transfusion and then returned to close to the baseline values seen in the RCP group (0.47 and 2.9 x 10(3) ng/microL [corrected], respectively) throughout the monitored period (p<0.05). C3a (169 vs. 116 ng/microL) [corrected] and IL-6 (29 vs. 6 pg/mL) reached higher plasma concentrations in the WB group (n = 11) than in the RCP group (n = 10). Phagocytosis of opsonized Escherichia coli was increased in neutrophils and monocytes and lasted up to 7 days after the transfusion of whole blood. CONCLUSION: Autologous WB induces a modest immunomodulation, but this effect is not observed upon transfusion of autologous blood components.